Immigration and growth in the economy Spanish (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This article analyses the complex interaction between population and economicgrowth and the various effects of immigration on the Spanish economy in recent years (2000-05). Not only does it describe the magnitude of economic flows (product,employment, income and expenditure) in the Spanish economy but also their imbalances and the role that immigration has played.
Keywords: Immigration; employment; Spanish economic growth; economic imbalances